Evaluación del proceso de reclutamiento y selección de personal bajo el régimen de la Losep del Hospital Regional Isidro Ayora, 2017 - Rodríguez Jaramillo, Samira Elizabeth. (2018)
In the present titling work called Evaluation of the Process of Recruitment and Selection of Personnel under the Regime of the LOSEP of the Isidro Ayora de Loja Hospital 2017, the administrative activities performed in the merit and opposition competitions were evaluated, determining if they were in agreement to the development of the Technical Staff Selection Standard, as well as to determine the efficiency and effectiveness achieved in the development of each of the stages of the personnel selection process; likewise determine the achievement of objectives and compliance with laws and regulations, which are related to the public sector, which is why the development of their administrative activities must be framed in principles of quality, efficiency and effectiveness, taking advantage of the available resources. With the application of the evaluation through indicators it was possible to determine the existence of errors present in the process in question, which can be corrected with the application of the pertinent recommendations, which will be present in the investigation, document that will contain the result of the application of the evaluation indicators. The evaluation by indicators was integral to the processes of merit and opposition contests developed in the Hospital Isidro Ayora de Loja, is a systematic, critical and detailed evaluation of the activities and administrative information systems using the methods: deductive, analytic-synthetic and techniques such as interview and application of indicators in order to correctly evaluate the development of the evaluated activities and systems, and thereby determine the shortcomings of the process so that decisions can be made to improve the productivity of the entity that executes selection processes of personal